1997
DOI: 10.1038/sj.bjp.0700877
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C isoenzymes in rat and human cardiovascular tissues

Abstract: 1 We have compared the expression of protein kinase C (PKC) activity and immuno-detectable isoenzymes in cytosolic and membrane extracts of rat and human cardiovascular tissues (heart, kidney, aorta, saphenous vein). Experiments were performed in raw extracts and upon combined diethylaminoethylcellulose (DEAE) and phenylsepharose column chromatography. 2 PKC activity that bound to DEAE mostly eluted with 200 mM NaCl. DEAE-puri®ed PKC from all tissues except rat kidney bound almost quantitatively to phenylsepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 37 publications
0
45
0
2
Order By: Relevance
“…However, based on those results, it is widely accepted that PKC-, -, -, and -are present in adult rat isolated cardiomyocytes. [18][19][20][21][22] We demonstrated in preliminary experiments that PKC-, -, and -are the dominant isoforms in isolated cardiomyocytes from both young-adult and middle-aged rats, although a small amount of PKC-ll is also present. Therefore, we used these 4 isoforms to investigate the age-related changes in PKC isoform expression in the present study, which demonstrated that only PKC-decreased in older cardiomyocytes.…”
Section: Changes In Pkc Isoform Expression With Agingmentioning
confidence: 99%
“…However, based on those results, it is widely accepted that PKC-, -, -, and -are present in adult rat isolated cardiomyocytes. [18][19][20][21][22] We demonstrated in preliminary experiments that PKC-, -, and -are the dominant isoforms in isolated cardiomyocytes from both young-adult and middle-aged rats, although a small amount of PKC-ll is also present. Therefore, we used these 4 isoforms to investigate the age-related changes in PKC isoform expression in the present study, which demonstrated that only PKC-decreased in older cardiomyocytes.…”
Section: Changes In Pkc Isoform Expression With Agingmentioning
confidence: 99%
“…The PKC family consists of at least 12 different isoforms, and the characteristics of the 3 subclasses have been reviewed in detail (173,190,619,838). Adult cardiac myocytes in most mammalian species express four major isoforms, including classical PKC-␣, novel class PKC-␦ and -, and to a lesser extent atypical PKC- (213,713,714). Several pathophysiological conditions and heart failure in humans are associated with increased expression of PKC-␣ and -␦, plus the appearance of PKC-␤, another classical isoform (77,648).…”
Section: Signaling Upstream From Pkcmentioning
confidence: 99%
“…All isoforms express distinct enzymological properties, differential tissue distribution, different substrate specificity, and specific subcellular localization with distinct modes of cellular regulation (4,6,9,18,23,36,38). For example, PKC␣, ␦, ⑀, and , but not PKC␤, which is strongly expressed in cardiomycytes, were detected in rat MC as determined by Western blotting (18,19,42).…”
mentioning
confidence: 99%